Advancing Rural Electrification in Ghana: Sustainable Solutions and Emerging Trends in Solar Energy Utilization - Jones Lewis Arthur; Michael Gameli Dziwornu; Paweł Czapliński; Tomasz Rachwał; Hope Kwame Fiagbor (Energies)
This study examines the integration and sustainability of solar energy technologies as a tool for rural electrification in Ghana, using the Lofetsume community as a case study. Persistent electricity access deficits in rural areas, coupled with unreliable grid systems and high energy costs, underscore the need for alternative energy solutions. Through semi-structured interviews and surveys, the study explores community perspectives and expert views on the viability of solar energy in rural Ghana. Findings reveal strong grassroots support for solar energy due to its reliability and environmental benefits, despite barriers such as high upfront installation costs and maintenance challenges. The study recommends multi-stakeholder partnerships, innovative financing models, and capacity-building initiatives to enhance solar energy adoption. By prioritizing solar energy technologies, the government, private sector, and local communities can collaborate to develop sustainable and affordable electrification solutions, ultimately improving living standards in remote areas and contributing to Ghana’s broader energy sustainability goals.